2001
DOI: 10.1046/j.1523-1755.2001.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole inhibits human peritoneal mesothelial cell proliferation in vitro and attenuates rat peritoneal fibrosis in vivo

Abstract: This study suggests that dipyridamole may have therapeutic potential in treating peritoneal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…TGF-β production and the activated signal pathway are important mediators leading to PF [13,14]. In addition, TGF-β is associated with PF in rat models [15,16]. These results further support the central role of TGF-β in PF.…”
Section: Introductionmentioning
confidence: 67%
“…TGF-β production and the activated signal pathway are important mediators leading to PF [13,14]. In addition, TGF-β is associated with PF in rat models [15,16]. These results further support the central role of TGF-β in PF.…”
Section: Introductionmentioning
confidence: 67%
“…5,7,8,[15][16][17]27,28 Previous studies have found no significant association between peritoneal wall thickness by US and peritonitis frequency. 15,[17][18][19] On the contrary, however, we found for the first time, a positive correlation between peritoneal thickness and episode of peritonitis (R 2 ¼ 0.933, Figure 4C).…”
Section: Discussionmentioning
confidence: 99%
“…Although the definitive diagnosis of PFS can be made by peritoneal biopsy, ethical issues, difficulty of the process and insufficient knowledge of PFS are the major obstacles for routine clinical application of peritoneal membrane biopsy. 3,[5][6][7][8][9][10] Measurement of cytokines levels which are responsible in PFS progression can be an alternative diagnostic tool. 3 However, there is no consensus on the time and the frequency of cytokines monitoring in the diagnosis of PFS.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the cells along with the supernatants were collected after scraping, and cAMP levels were analyzed using an ELISA kit. 11 In endothelial cells grown in parallel and treated similarly, the monolayers were inspected microscopically for intactness, the protein content was measured, and the data were normalized to protein content.…”
Section: Camp Synthesismentioning
confidence: 99%